Restorative Justice Approach as an Alternative Criminal Case Resolution in Realizing Effective and Efficient Justice - Wahyudhi, Dheny; Rahayu , Sri; Sudarti, Elly; Liyus, Herry (Jurnal Sains Sosio Humaniora, 2024)
This research aims to find out how the regulation of restorative justice as an alternative in resolving effective and efficient criminal cases and to find out how the settlement of criminal cases through a restorative justice approach in realizing effective and efficient justice. For this reason, researchers are interested in conducting research with the title restorative justice approach as an alternative to criminal case settlement in realizing effective and efficient justice. This research is a normative juridical research. The results of the study found that the regulation of rhetorative justice is regulated internally in each law enforcement institution of the police, prosecutor's office and court. The orientation is no longer on punishment but shifts to restoring the original situation through peace efforts of the parties, both victims, perpetrators and communities affected by criminal acts. so that it can present an effective and efficient justice both in terms of time and costs incurred. Suggestions so that the settlement of criminal offenses with a restorative justice approach runs effectively and efficiently, it is necessary to equalize the perceptions of each law enforcement agency, both the police, prosecutors and courts regarding what criminal offenses can be resolved through a restorative justice approach and the time period given in resolving criminal offenses with a restorative justice approach and needs to be regulated in the form of a law.